Precipitation-hardened high-entropy alloys for high-temperature applications: A critical review. (November 2019) - Cao, Boxuan; Yang, Tao; Liu, Wei-hong; Liu, C.T.
Abstract: Abstract : Conventional alloy design based on a single primary element has reached its limits in terms of performance optimization. An alloy design strategy with multi-principal elements has recently been uncovered to overcome this bottleneck. Multicomponent alloys, generally referred to as high-entropy alloys (HEAs), exhibit many promising properties, especially outstanding mechanical performance at cryogenic, ambient, and elevated temperatures. In this article, we focus on precipitation-hardened HEAs, which are potential candidates for next-generation structural materials, especially at high temperatures. The key issues involved include precipitation behaviors, phase stability, and phase control, all of which provide useful guidelines for further development of high-temperature materials with superior performance. In particular, we address the formation of cellular γ′ precipitates at grain boundaries, which is closely related to the embrittlement of HEAs at intermediate temperatures. Critical issues and design strategies in developing HEAs for high-temperature applications are also discussed.